Constitutional Secularism and Religious Fundamentalism in Italy and Europe: Considerations Stemming from Judicial Decisions (Italian Review of Legal History, 2017)
The Author addresses the relationship between secularism and religious fundamentalism within the italian constitutional system.Through an in depth investigation of the most significant case-law both at the national and at the supranational level, the Author questions how could religious fundamentalisms be reconcilied with the individual’s fundamental rights.The Author then goes on by investigating the dilemma surrounding an approach to the relationship between the secularity of the State and religious forms of radicalization by underling the key role played by the so called “secularistic method” together with a case-by-case evaluation in the composition of conflicts among the individual, the community and the State.
Keywords: Multiculturalism; Secularism; Fundamental Rights, Protection of; Women, Rights of